Importance of Insulin Immunoassays in the Diagnosis of Factitious Hypoglycemia - Nalbantoğlu Elmas, Özlem (J Clin Res Pediatr Endocrinol, 2014)
We report two cases emphasizing the importance of insulin assays for evaluation of hypoglycemia in diabetic patients. Case 1 was a 96/12-year-old female patient with type 1 diabetes mellitus and case 2 was a 1010/12-year-old male patient with DIDMOAD. Both patients were on a basal-bolus insulin regimen. Both were admitted because of persistent hypoglycemia. Analyses of serum samples obtained at the time of hypoglycemia initially showed low insulin and C-peptide levels. Recurrent episodes of unexplained hypoglycemia necessitated measurement of insulin levels by using different insulin assays, which revealed hyperinsulinemic hypoglycemia with low C-peptide levels, findings which confirmed a diagnosis of factitious hypoglycemia. Surreptitious administration of insulin should not be excluded in diabetic patients with hypoglycemia without taking into account the rate of cross-reactivity of insulin analogues with the insulin assay used.